VOCATIONAL COUNSELLING THEORY: REVIEW AND CHALLENGES IN KANO STATE, NIGERIA - MUHAMMED, Dahiru; IBRAHIM, Ahmad; BALARABE, Shehu; ABUBAKAR, Nabila (Journal of Professional Counselling, 2025)
This paper critically reviewed Vocational Counselling Theory: Review and Challenges in Kano State, Nigeria. Effective vocational counselling can substantially impact adolescents' growth and development in a dynamic socioeconomic environment by offering clear pathways for both professional and personal development. The major challenges facing Vocational Counselling among Adolescents in Kano State, Nigeria are Sociocultural Factors, Educational System, Economic constraints, Infrastructure and Resources, Awareness and Attitudes. Based on the discussions of this study, it was suggested that; Educational policy makers should include vocational counselling in the curriculum since it can offer ongoing directions and expose students to a wide range of job alternatives.